2010
DOI: 10.1080/10510970903405997
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Management as Unfinished Business: Shifting Boundaries in the Context of Infertility

Abstract: Privacy dilemmas are prevalent for women who experience a fertility problem. In this study, we use communication privacy management (CPM) theory to explore how privacy boundaries shift over time as women cope with infertility. Based on interviews with 23 women, we found that women described distinctive patterns of shifting privacy boundaries, including situations in which the experience of infertility served as a change agent, patterns in which women became more or less open over time, and patterns that indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…We also found support for Bute and Vik's (2010) claim that the experience of a health problem, such as infertility, can be a catalyst for shifting privacy boundaries. At times, the decision to open this boundary was catalyzed by a need for social support.…”
Section: Discussionsupporting
confidence: 65%
“…We also found support for Bute and Vik's (2010) claim that the experience of a health problem, such as infertility, can be a catalyst for shifting privacy boundaries. At times, the decision to open this boundary was catalyzed by a need for social support.…”
Section: Discussionsupporting
confidence: 65%
“…This study acknowledges the ongoing difficult decisions individuals make in disclosing and discussing their infertility (Bute & Vik, 2010). Like previous studies, this study found that part of their responses depended upon the meaning assigned to the other person's questions or comments (Bute, 2009).…”
Section: Theoretical Implicationssupporting
confidence: 65%
“…Yet, these time-oriented markers seemed to give couples one concrete criterion for privacy rule development in the midst of a chaotic and unpredictable situation. By highlighting the way that privacy management shifts over time (Bute & Vik, 2010) and drawing attention to the role of temporality, this study contributes to continuing scholarly conversations that frame privacy management as an ongoing, ever-shifting process rather than a one-time event (e.g., Caughlin et al, 2009).…”
Section: Theoretical Implicationsmentioning
confidence: 98%
“…In-depth interviews are an appropriate method for studying privacy management, especially when practical and ethical considerations impede direct observation or recording of naturally occurring conversations (Bute & Vik, 2010). Moreover, participants can benefit from catharsis during the interview.…”
Section: Interviewing Proceduresmentioning
confidence: 99%